1978
DOI: 10.1037/0022-3514.36.12.1490
|View full text |Cite
|
Sign up to set email alerts
|

Sentencing strategies and justice: Effects of punishment philosophy on sentencing decisions.

Abstract: The cognitive processes underlying sentencing decisions made by college student subjects in a judicial decision-making experiment were examined. Subjects were asked to follow one of three punishment strategies (retribution, rehabilitation, or deterrence). In addition, the type of crime and the physical attractiveness of the offender were systematically varied. Length of recommended prison term, subjects' judgments of seriousness of the crime, likelihood of recidivism, and blame attributed to offender and victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 10 publications
7
58
1
4
Order By: Relevance
“…Our findings are highly consistent with previous research showing the importance of retributive desires in punishing criminals (Carlsmith, 2006;Carlsmith, Darley, & Robinson, 2002;Ellsworth & Ross, 1983;McFatter, 1978). We did not ask the respondents to explicitly justify their support for civil commitment, but had we done so there probably would have been strong consensus that it was based on worries that the perpetrator would commit more crimes if given the opportunity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are highly consistent with previous research showing the importance of retributive desires in punishing criminals (Carlsmith, 2006;Carlsmith, Darley, & Robinson, 2002;Ellsworth & Ross, 1983;McFatter, 1978). We did not ask the respondents to explicitly justify their support for civil commitment, but had we done so there probably would have been strong consensus that it was based on worries that the perpetrator would commit more crimes if given the opportunity.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the social psychological literature is rife with examples in which people are inaccurate about the basis of their attitudes and behavior (Ellsworth & Ross, 1983;Nisbett & Wilson, 1977;Wilson, 2002). More to the point, recent empirical work has demonstrated that although people frequently articulate incapacitative motivations in sentencing criminal offenders, their behavior is more consistent with the retributive perspective (Carlsmith, 2006;Carlsmith & Simester, 2006;Feather, 2002;McFatter, 1978). For example, Carlsmith (2006) asked participants to punish offenders under a variety of circumstances and found that people were highly sensitive to variation of factors that were relevant to a retributive theory of punishment, but largely ignored variation of factors that were critical to utilitarian perspectives.…”
Section: Introductionmentioning
confidence: 88%
“…Rehabilitation, retribution, incapacitation, and deterrence (of the offender or would-be offenders) are the primary goals of sentencing identified by researchers (Carlsmith, Darley, & Robinson, 2002;Carroll et al, 1987;Darley, 2002;Darley & Pittman, 2003;McFatter, 1978McFatter, , 1982McKee, 2005, unpublished doctoral dissertation;Roberts & Stalans, 1998), and surveys indicate that all of these sentencing goals or strategies are endorsed by the public depending on the circumstances (Roberts & Stalans, 1998). The choice of sentencing goal may be influenced by dispositional and situational factors, with contextual factors concerning the offender or the offense influencing which strategy is chosen in any one particular circumstance.…”
Section: Sentencing Goals Values and Personality Characteristicsmentioning
confidence: 97%
“…However, we must recognize that finer distinctions among goals are not only possible conceptually, but also that some research has found differences among goals such as punishment and deterrence (McFatter, 1978). We may resolve this In two ways.…”
Section: Sentencing Goals Page 21mentioning
confidence: 99%